Water relations of field grown Pomegranate trees (Punica granatum) under different drip irrigation regimes - Intrigliolo, Diego S.; Nicolás, Emilio; Bonet, Luis; Ferrer-Talón, Pedro J.; Alarcón, Juan J.; Bartual, Julián (2017)
Pomegranate (Punica granatum L) is a deciduous fruit tree native of central Asia included in the so-called group of minor fruit tree species, not widely grown but of some importance in the south east of Spain. Fruit consumption interest is due to the organoleptic characteristics and to the beneficial effects on health. Pomegranate tree are considered as a culture tolerant to soil water deficit. However, very little is known about pomegranate orchard water management. The objective of this work was to characterize, for the first time in P. granatum, water relations aspects of applied significance for irrigation scheduling. Trees under different irrigation regimes were used and midday stem water potential (psi(stem)) and midday leaf gas exchange were periodically measured over the course of an entire season. During spring and autumn, psi(stem) did not show significant differences between irrigation treatments while there were considerable differences in leaf photosynthesis and stomatal conductance, suggesting a near-isohydric behaviour of pomegranate trees. This might explain why the signal intensity of psi(stem) was lower than those of gas exchange indicators during the experimental period. Thus, leaf photosynthesis rates and stomatal conductance might have a greater potential for irrigation scheduling of pomegranate trees than psi(stem) measured at solar noon. (C) 2010 Elsevier B.V. All rights reserved.